Untangling Tales of Tropical Sardines: Local Knowledge From Fisheries in Timor-Leste - Hunnam, Kimberley; Carlos, Imelda; Hammer, Michael P.; Dos Reis Lopes, Joctan; Mills, David J.; Stacey, Natasha (Frontiers in Marine Science, 2021)
Tropical sardines (Family Clupeidae) are an important component of many marine fisheries in the Indo-West Pacific region. In Timor-Leste, a small, less-developed country within this region, ‘sardiña’ are some of the more commonly caught and consumed fish. Yet there is little published information from Timor-Leste about the species composition of these fisheries, nor their biology or ecology. We document the knowledge of Timorese fishers on nine locally distinguished sardine types that contribute to fisheries, and relate these to at least nine species: four species of ‘Flat-bodied Sardinellas’ (Sardinella subg. Clupeonia spp.), one species of ‘Round-bodied Sardinella’ (Sardinella subg. Sardinella lemuru), two species of ‘Tropical Pilchards’ (Amblygaster spp.) and a ‘Tropical Herring’ species (Herklotsichthys quadrimaculatus), all from the Clupeidae family; and one Dussumieria species from the Dussumieriidae family. We record variations in local sardine names across the country and document aspects of fishers’ knowledge relevant to understanding and managing the fisheries, including local sardine species’ seasonality, habitat, movements, interannual variation, as well as post-harvest characteristics in relation to perishability. In general, local names relate more closely with groups of species than individual species, although some names also distinguish fish size within species-groups. The local knowledge identified in this study has immediate application to inform fisheries monitoring and management, and to identify areas for future research. Notably, Timorese fishers recognize and make use of the strong association between some sardine species-groups and seasonally turbid river plumes. While further research is required to understand the underlying mechanisms of this association, this emphasizes the need to consider coastal fisheries and fisher livelihood impacts when assessing any plans or proposals that may alter river flow or water quality. Fishers also recognize migratory behavior of some sardine species, in particular the Flat bodied Sardinellas (S. gibbosa and others) along the north-west coast of Timor-Leste and across the border into Indonesian West Timor. Such insights complicate and need to be accounted for in initiatives for co-management or community-based management of Timor-Leste’s coastal waters and their fisheries.